Evaluation of waste management and hygienic-sanitary conditions of a pizzeria located in the north of Bahia (Research, Society and Development, 2021)
Waste is one of the main causes of increased costs in the production of meals. Thus, the objective was to evaluate waste management and the hygienic-sanitary and microbiological conditions of food and surfaces in a pizzeria in northern Bahia. This is a cross-sectional, qualitative and quantitative study. The hygienic-sanitary diagnosis was carried out through the application of a checklist according to RDC nº 216/2004, ANVISA, and the microbiological analysis performed for the counting of total coliforms, Escherichia coli, Staphylococcus aureus and the presence / absence of Salmonella, in the food samples . For the analysis of surfaces and equipment, the swab technique and the counting of total coliforms and Escherichia coli were used through the Petrifilm Coliform Count Plate 3M® analysis system. Acceptable values ​​of total coliforms were observed on the pizza, tomato and chicken board, with values ​​of 1.40 x 10³ UFC / cm², 1.04 x 10³ UFC / g, 1.70 x 10³ UFC / g, respectively; and unacceptable in the food processor, corresponding to 4.88 x 10³ UFC / cm². It was found 1.3 x 10³ UFC / mL, total coliforms in the water, where it should be absent. There were no Escherichia coli colonies or Salmonella in the samples. As for the hygienic-sanitary conditions, the pizzeria was classified in group 3 (0 to 50% of the items' service), according to RDC nº 275/2002. Therefore, the presence of a technician in charge of food service is necessary, presenting a direct relationship in the control of waste and hygienic-sanitary, promoting corrective actions that provide the reduction of risks associated with food contamination and optimization of operating costs.